If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(p+6)=4(p+4)=-8
We move all terms to the left:
3(p+6)-(4(p+4))=0
We multiply parentheses
3p-(4(p+4))+18=0
We calculate terms in parentheses: -(4(p+4)), so:We get rid of parentheses
4(p+4)
We multiply parentheses
4p+16
Back to the equation:
-(4p+16)
3p-4p-16+18=0
We add all the numbers together, and all the variables
-1p+2=0
We move all terms containing p to the left, all other terms to the right
-p=-2
p=-2/-1
p=+2
| 2x-6=5x+6 | | 7n-n=16 | | .75y=11.25 | | 10.14+y=25.14 | | 4.5y=67.5 | | 5^x=35 | | 2x+3/2=5+x | | 100=2(3+6n)-2 | | -10y^2+33y-26=0 | | 17/5x-4x=-2=-2x+21/20 | | 3x+42-x=10 | | 2/3x+6=1/2x=1/4 | | 102+19m=330 | | 31n-102=425 | | 38=-8+5(x+4) | | X²(x-9)(2x+1)=0 | | 5p+13/2=14 | | 1/12y-2=-10 | | -(5r+4)=-2(2+5r)-5 | | 1/12y+3=-15 | | 160=120/a(144) | | y/8+8=-13 | | 3x-7x=-4(x-6)-8(7-x) | | 6x²+x-15=0 | | (x+4)²-8x=0 | | -3(4p-2)=21-7p | | -4(-3+6x)=-15+3x | | 6=-3x-33 | | -2(8n-3)=-90 | | 5x-24=3x+76 | | 128=-8(m-2)-6m | | g=9.81*50/0.5^2 |